2002
DOI: 10.1073/pnas.092136199
|View full text |Cite
|
Sign up to set email alerts
|

Tau is essential to β-amyloid-induced neurotoxicity

Abstract: Senile plaques and neurofibrillary tangles, the two hallmark lesions of Alzheimer's disease, are the results of the pathological deposition of proteins normally present throughout the brain. Senile plaques are extracellular deposits of fibrillar ␤-amyloid peptide (A␤); neurofibrillary tangles represent intracellular bundles of self-assembled hyperphosphorylated tau proteins. Although these two lesions are often present in the same brain areas, a mechanistic link between them has yet to be established. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
535
2
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 739 publications
(580 citation statements)
references
References 43 publications
33
535
2
10
Order By: Relevance
“…Interestingly, Aβ-induced cytotoxicity was shown to be tau-dependent in primary neuronal culture with either genetic depletion of tau, or using an undifferentiated neuronal culture (which has a lower tau level than differentiated neurons) [56,57]. Tau knockout studies revealed that the Aβ-induced axonal transport deficits and impairment of hippocampal LTP were mediated by tau [58,59].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%
“…Interestingly, Aβ-induced cytotoxicity was shown to be tau-dependent in primary neuronal culture with either genetic depletion of tau, or using an undifferentiated neuronal culture (which has a lower tau level than differentiated neurons) [56,57]. Tau knockout studies revealed that the Aβ-induced axonal transport deficits and impairment of hippocampal LTP were mediated by tau [58,59].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%
“…Although most of the studies of excitability have used mice with disturbed APP expression and metabolism, tau is important to mention because it appears to play a critical role in Ab-driven pathology (51)(52)(53). Normally, tau is an important component of the cytoskeleton and subject to phosphorylation by diverse kinases.…”
Section: Pass the Salt: Mechanisms Of Seizures In Mouse Models Of Admentioning
confidence: 99%
“…Furthermore, Aβ-induced neurodegeneration requires tau expression and may involve the intracellular assembly of pathological tau filaments (59,60). The colocalization of ΔTau with both intraneuronal and extracellular Aβ deposits suggests that Aβ accumulation may initiate caspasecleavage of tau.…”
Section: Figurementioning
confidence: 99%